THE EFFECT OF PRODUCT QUALITY, BRAND AWARENESS AND PRICE ON CONSUMER PURCHASE DECISIONS AT BLACKDOG STORE SIDOARJO - Fungki Irawan Hartoyo; Nuryadi (International Journal of Economics, Science, and Education, 2024)
This research aims to analyze the influence of product quality, brand awareness and price on consumer purchasing decisions at the Blackdog Store Sidoarjo. The background to the problem of this research is competition between businesses, as well as efforts to increase the existence of distros and the lack of public trust in local products such as distros. Seeing this phenomenon, researchers conducted an analysis of the influence and relationship of product quality, brand awareness and price on consumer purchasing decisions at the Blackdog Store Sidoarjo. The analysis used in this research is quantitative and the sampling technique used is purposive sampling with the number of respondents obtained being 45 respondents. Data collection was carried out using questionnaires. The data analysis technique in this research uses multiple linear regression analysis via the T test and F test. The results of this research show that product quality, brand awareness and price have a significant partial and simultaneous influence on purchasing decisions at the Blackdog Store Sidoarjo.